Da epistemologia moderna à epistemologia complexa de Edgar Morin: repercussões sobre o humanismo - MONTEIRO NETO, Benedito da Conceição (Universidade Federal do Pará, 2022)
Our objective, in the present work, is dedicated to demonstrating the main epistemological elements of the complexity elaborated by Edgar Morin in general contrast with the principles of the modern method of Descartes. We start from the following guiding questions: how does the passage from modern ordered knowledge to complex organized knowledge occur and how does this knowledge culminate in a conception of humanism? The hypothesis we defend is that Morin's principles of complexity are exposed as a critical dialogue about the limitations of the modern method, pointing out how the last one has an ambivalent impact on science and society under the name of degenerate humanism and a regenerated humanism. Methodologically, we discuss, firstly, the conception of science and method in modernity, starting with the arguments that precede and formulate the organization of a quantitative method of knowledge, having as a central axis the contributions of Descartes in his main works (1952). The second part of the text turns to the conception of science and method according to the contributions of the epistemology of complexity, proposed by Edgar Morin (1996, 2011, 2015, 2016), where we present the main intelligibilities of his theory: the dialogic principle, the recursive principle, the hologrammatic principle. In the third and last part of the text, we compare complex thinking and modernity based on the concept of humanism. Initially, we expose the reading of modernity by complexity, highlighting the category of rationalization. Then, we explain how the modern method has repercussions in contemporary times with the advent of the action ecology. Finally, we present a reconstruction of an alternative method and knowledge, capable of dealing with uncertainties, culminating in the proposal of a regeneration of humanism.